A new morning - Armocida, Giuseppe; Cardinale, Adelfio Elio (Medicina Historica, 2017)
In this new day, our Society has renewed its official journal. Sixty years have passed since the Rivista di storia delle scienze mediche e naturali changed its name to Rivista di Storia della Medicina, and now the new series of Medicina Historica begins. In the history of medicine the winds are not always constant...